Dynamic Modeling and Vibration Characteristics for a High-Speed Aero-Engine Rotor with Blade Off - Longkai Wang; Yijun Yin; Ailun Wang; Xing Heng; Miao Jin (Applied Sciences, 2021)
Blade off that occurs during operation will generate a sudden imbalance excitation and make the rotor become inertially asymmetric, which leads to large instantaneous impact load and induces more complex rotor dynamic phenomena. In order to study the transient dynamic characteristics for complex rotors suffering from blade off, a mathematical model for solving the response of the gas generator rotor in the aero-turboshaft engine is established based on the FE method and DOF condensation, in which the complex structural characteristics, transient impact load, and inertia asymmetry of the rotor are considered. The complex impeller structure is modeled by piecewise linear fitting with cylindrical beam elements and tapered beam elements. Without loss of generality, the modeling method suitable for complex rotors is verified through a general complex test rotor with modal experiments. Based on this, the responses are solved for carrying out parametric studies and an understanding of the transient dynamic characteristics of the rotor under the extreme working conditions of blade off. The results show that the blade off has a great impact effect on the time-domain waveform, frequency components, and rotor orbits. At the instantaneous stage after blade off, the complex motion is composed of synchronous motion and some lower-order natural modes excited by blade off. Although the transient responses with blade off at different rotational speeds have similar time-varying characteristics, the impact factor is sensitive to the rotating speed. Most important is that the parameter of the blade off location will not only have a significant effect on the impact factor, but also on the frequency spectrum. These dynamic characteristics as well as impact effect provide certain guidance for the fault recognition and dynamic analysis to these complex rotors suffering blade off.